Fog computing as a critical link between a central cloud and iot in support of fast discovery of new hydrocarbon reservoirs - Goscinski, A.M. (Springer Verlag, 2018)
The overall process of discovering hydrocarbon traps, starting with geological exploration through to Seismic Data Processing (SDP) is very expensive and time consuming. In the real-world, the oil and gas production relies on how soon seismic data is computationally processed. The ability for an oil and gas company to perform seismic computation at higher speed within shorter time provides competitive advantage in the race to discover new hydrocarbon reservoirs. We are convinced that the current state of research in areas such as cloud computing, fog computing, and edge computing will make a major change. The goal of this paper is to present the first step towards the development of such a three-level system and show its feasibility in the context of a model for hydrocarbon exploration and discovery operation. Â© ICST Institute for Computer Sciences, Social Informatics and Telecommunications Engineering 2018.